Aksi Irasional dan Keseimbangan Sosial dalam Perubahan Sosial akibat Penggunaan Mesin Pertanian Modern pada Pengelolaan Sawah - Wiroto, Dondick Wicaksono; Duengo, Wahyu Nur’azhim; Ibrahim, Ridwan; Rahmatiah (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2023)
The inclusion of modern agricultural machinery, combine harvesters, in a village can have two social impacts: (1) the loss of a culture of mutual cooperation with a system of reciprocity between landowners and farm workers, and (2) a large loss of employment opportunities for farm workers in managing agricultural land in their villages. This can certainly make the social balance in the village disturbed, even so in Permata Village this balance is maintained. This social balance was researched using Vilfredo Pareto's individual action analysis framework and using qualitative approaches and case study methods. Social facts are moulders of individual actions, and rational actions exist only within economic facts, so a number of problems that are not resolved by economic means require consideration of irrational factors. The informant's statements regarding the actions they performed were analyzed to be categorized as irrational, which was then discussed with the concept of residue and derivation from Pareto. This study succeeded in explaining that there are four main factors of irrational actions that maintain social balance in the village, these four factors are reduced to coincidence factors and factors of systematic and appropriate interpretation and way of responding by the village government elite.